Adrenal Disease in Small Mammals - Jekl, Vladimir (The veterinary clinics of North America. Exotic animal practice, 2025)
Adrenal gland disease has been described as a rare disease in pet rabbits and rodents. Hyperadrenocorticism with excessive secretion of corticosteroids is most commonly observed in guinea pigs and hamsters, with dermatologic signs similar to those seen in dogs. Diagnosis is based on clinical signs, diagnostic imaging such as abdominal ultrasound, and determination of the blood hormone concentrations. In guinea pigs, an adrenocorticotrophic hormone stimulation test with the measurement of salivary cortisol or corticosterone concentrations is recommended. The recommended treatment of adrenal disease in guinea pigs and hamsters is oral administration of trilostane or ketoconazole; surgical treatment is also possible.
Keywords: křečci praví; Trilostane; Rabbit; Hyperadrenocorticism; Cushing; Adrenal; nemoci nadledvin; Hypertestosteronism; zvířata; Guinea Pigs; Hamster; morčata; nemoci hlodavců; králíci; Cricetinae; Animals; Adrenal Gland Diseases; Rodent Diseases; Rabbits; Guinea pig